Analysis of temperature dependence on solar energy radiation pattern at different wavelengths - M. A., Humayun; F., Malek; Syafruddin, Hasan (Asian Research Publishing Network, 2014)
This paper presents a theoretical analysis of the effect of atmopharic temperature and the light emission wavelength from the Sun on the solar energy radiation pattern. In this study, we have investigated extensively the radiant emittance phenomena of the solar radiation by using Planck’s law of radiation and the Stephan-Boltzmann’s law. Wavelength dependence of radiant emittance has been analyzed at three different temperatures. We have considered the three different temperatures such as room temperature i.e. 300K, 275K as temperature below room temperature and 325K as the temperature above room temperature. The three different temperatures considered in this present analysis are chosen very close to each other to investigate exactly the effect of wavelength on the radiation pattern of the emitted energy from the Sun due to the small change in temperature. Further the effect of temperature on radiant emittance has also been investigated at three different wavelengths. The three wave lengths considered in our research work are 1.55µm, 1.3µm and 0.89µm respectively. The range of wavelength has been considered within the limit of 0.89µm - 1.55 µm because this range of wavelength corresponds to the energy bandgap of the semiconductor materials from 0.8 eVto 1.4 eV, which are widely used for solar cell fabrication. The investigation of the temperature dependence with maximum wavelength of the radiated energy was carried out up to the black body temperature. Numerical results obtained have been analyzed. It is revealed from the numerical analysis that not only the atmospheric temperature but also the wavelength of the emitted light from the Sun affects the radiation pattern significantly.